A Review of Ethnomedicinal Plants as Potential Anthelmintic Agents to Alternatively Control Gastrointestinal Nematodes of Ruminants in South Africa - Lindokuhle Christopher Mhlongo; Cresswell Mseleku; Thando Tenza; Sylvester Werekeh Fomum; Lyndy Joy McGaw; Abubeker Hassen; Ignatius Verla Nsahlai (Journal of Parasitology Research)
Small ruminant production is one of the most important animal productions for food security in the world, especially in the developing world. Gastrointestinal nematode (GIN) infection is a threat to this animal’s production. Conventional drugs that are used to control these parasites are losing their efficacy due to the development of resistant parasites. These drugs are not biologically degradable, taint meat products and are also expensive for communal farmers. Hence, research is now exploring ethnomedicinal anthelmintic plants for an alternative remedy. The objective of this paper was to review ethnomedicinal plants as a potential alternative to unsustainable commercial anthelmintics. This review sought to understand common GINs infecting ruminants, resistance manifestation in GINs to conventional treatment, reasons communal farmers choose ethnomedicine, and modes of action in anthelmintic plants. It also examined the usage of plants and plant parts, dosage forms, methods for improving bioactivity, convectional validation procedures, and restrictions on ethnomedicinal plant use as anthelmintics in ethnomedicine. Such insight is essential, as it highlights the importance of ethnoveterinary medicine and ways to adopt or improve it as a potential alternative to conventional anthelmintics.